90-5h=4h

Simple and best practice solution for 90-5h=4h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90-5h=4h equation:


Simplifying
90 + -5h = 4h

Solving
90 + -5h = 4h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4h' to each side of the equation.
90 + -5h + -4h = 4h + -4h

Combine like terms: -5h + -4h = -9h
90 + -9h = 4h + -4h

Combine like terms: 4h + -4h = 0
90 + -9h = 0

Add '-90' to each side of the equation.
90 + -90 + -9h = 0 + -90

Combine like terms: 90 + -90 = 0
0 + -9h = 0 + -90
-9h = 0 + -90

Combine like terms: 0 + -90 = -90
-9h = -90

Divide each side by '-9'.
h = 10

Simplifying
h = 10

See similar equations:

| 7z+(-13z)=x | | 8x+13=-43 | | 8n=96-4n | | dy=2d-ax | | 3x^9y^7+18x^7y^6+21xy= | | 49=44+-2x | | 33-4x=9-8x | | 9z^2+18z= | | x+2x+135+(x+5)=360 | | 2x+14=-42-6x | | 2x-4=6(x-1) | | a(x)+a+d(y)=a+2d | | (x^2-4)(x^2-9)=7x^2 | | -(9x+1)=x | | 7x-15=6x+5 | | 5(2)/10(2)2=x | | 28-z*4=5 | | 4z+4=z-3 | | 6+9(4-7)2=x | | 2(3n+6)=8 | | 9-4/2*5=x | | 11=33x+8 | | -6/3=x | | 6x+a+2ax+3=(3+a)(2x+1) | | 5y+(-12y)=x | | 9x+45=-3(x-39) | | 22(134+x)=22(3x+550) | | 22(134+x)=11(3x+550) | | -8x-48=4x-24 | | h+-2= | | 3f+-12= | | 2p(p-3)+4= |

Equations solver categories